Digestibility of nine hybrid sorghum grains fed to finishing steers winter 1971-72 - R.L. McCollough; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 1973)
Nine hybrid sorghum grains representing hetero-yellow, all-waxy, white, part-waxy, and white endosperm were fed to finishing steers to determine digestibility. Hybrids were all planted on the same irrigated bottom field and harvested and stored separately till fed. The sorghum grains were dry-rolled and incorporated into 90% concentrate rations. Digestibilities were determined using chromic oxide.
Keywords: Cattlemen' s Day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station); 568; Beef; Digestibility; Grain sorghum; Steers